Boards of trustees must assume responsibility for making alcohol prevention on campus a top priority. Issue 1 (2nd January 2016) - DeJong, William
ABSTRACT: Few colleges have made the prevention of alcohol-related injuries and deaths an institutional priority, and even fewer have implemented prevention strategies with a solid evidentiary base. We look to presidents to provide leadership on this issue, but those who do are atypical. Boards of trustees should step in by asserting that student wellness be a primary focus in the institution's strategic plan, with specific, measurable goals; holding the president accountable for progress in reducing high-risk drinking and its consequences; and mandating a line item in the annual budget, with adequate staffing and revenues to put evidence-based practices in place. Boards will be more likely to respond when led to focus on the cost implications of the campus alcohol problem; the link between high-risk drinking and mission-critical institutional objectives such as academic performance, student engagement, and retention; and the institution's potential liability if evidence-based prevention strategies are not in place.